2003
DOI: 10.1021/bi034305c
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Thiol pKa Effects on the Folding Rate of a Disulfide Containing Protein

Abstract: The production of proteins via recombinant DNA technology often requires the in vitro folding of inclusion bodies, which are protein aggregates. To create a more efficient redox buffer for the in vitro folding of disulfide containing proteins, aromatic thiols were investigated for their ability to increase the folding rate of scrambled RNase A. Scrambled RNase A is fully oxidized RNase A with a relatively random distribution of disulfide bonds. The importance of the thiol pK(a) value was investigated by the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Aromatic thiols, for example, have already been shown to increase the folding rate of disulfide-containing proteins more than aliphatic thiols [30,31]. For a pharmaceutical excipient such as thiolated chitosans, the increased reactivity of the thiol group would further increase its beneficial properties over alkyl thiol chitosan and non-thiolated polymers.…”
Section: Aryl Thiolated Chitosansmentioning
confidence: 99%
“…Aromatic thiols, for example, have already been shown to increase the folding rate of disulfide-containing proteins more than aliphatic thiols [30,31]. For a pharmaceutical excipient such as thiolated chitosans, the increased reactivity of the thiol group would further increase its beneficial properties over alkyl thiol chitosan and non-thiolated polymers.…”
Section: Aryl Thiolated Chitosansmentioning
confidence: 99%
“…Recently, improved redox buffers have been used, such as aliphatic dithiols, synthetic peptides, and aromatic monothiols. 32,[34][35][36][37][38]116 Aliphatic dithiols, e.g. Furthermore, in previous studies by our group, it has been shown that aromatic monothiols (pK a 5.5-6.6) increased the folding rate and the overall yield of native protein compared to standard aliphatic thiols (pK a 8.5-10).…”
Section: Redox Buffermentioning
confidence: 86%
“…35 The thiol in its deprotonated form can act as a nucleophile or a leaving group, and thiol in a disulfide can act as a center thiol (Scheme 2). 35 Disulfide bond formation can be inhibited by the burial of reactive groups, such as protein thiol groups, protein disulfide bonds, and mixed disulfide bonds, in a stable tertiary structure. For instance, the burial of the disulfide bonds in stable tertiary structures prevents their reduction and reshuffling.…”
Section: 41mentioning
confidence: 99%
See 2 more Smart Citations